Stable sunflower oil oleogel from oil/water pickering emulsion with regenerated chitin. (July 2021) - Baraki, Senay Yacob; Jiang, Yang; Li, Xiang; Debeli, Dereje Kebebew; Wang, Bija; Feng, Xueling; Mao, Zhiping; Sui, Xiaofeng
Abstract: Pickering emulsion templating is a versatile technique in formulating highly networked oil-in-water emulsions applicable in foods, cosmetics, and pharmaceuticals areas. In this work, oleogels was prepared by oil-in-water Pickering emulsions using regenerated chitin (RCh) as the stabilizing particles. The effects of RCh concentrations (0.4/100–1.4 g/100 g) on the formation, rheology, and log-term stability of the emulsions and oleogles were investigated. It was found that the solid-like oloegel with a high concentration of liquid oil ( ≥ 98 g/100 g) could be obtained after evaporating of water from the emulsions. Shear-thinning behavior was observed at lower concentrations of RCh (0.4–0.6 g/100 g) and higher frequencies in the emulsions. An increase in the viscoelastic property was achieved. Oleogels containing higher concentrations of RCh (0.8/100–1.4 g/100 g) showed excellent resistance against coalescence and Ostwald ripening during the storage time. These oleogels also showed good thermal stability (no sign of oil leakages) when heated to 80 °C for 2 days. This emulsion templating approach is a feasible oil structuring strategy promising to be used in various applications. Graphical abstract: Image 1 Highlights: Oleogel was prepared via Pickering emulsion stabilized by regenerated chitin (RCh). The oleogel contains up to 98 wt% sunflower oil. RCh formed a strong network and effectively bind the oils. Oloegel showed higher gel strength (G'>10 5  Pa) and excellent structural stability.